Determination of Complications and Contraception Failure in East Java Province, Indonesia - Ida Farida1 , Lutfi Agus Salim2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Family Planning Programs in Indonesia is carried out by means of contraception which is an effort toprevent pregnancy. These efforts can be temporary, can also be permanent. But until now there has not beena 100% ideal method of contraception, because ideally a contraception is seen from the effectiveness, safe,cheap, aesthetic, easy to obtain, does not require continuous motivation, and minimal side effects. Acceptorsusing reversible contraception (aged 15-45 years) have a 1.8 chance of contraceptive failure. Within 1 yearof use, the reversible method fails as much as 1%. Achievement of cases of complications and contraceptivefailure in fertile age couples in East Java can be seen that cases have increased from early January 2019to the end of December 2019 with the achievement of 212 acceptors who experienced cases of failurefailure and 90 acceptors who experienced complications in the province of Java. East in 2019. The failureof contraception can be caused by various things, namely because of the method itself, termination of themethod by the acceptor, lack of discipline in using it or use errors. According to Lawrence Green, a person’shealth is influenced by two main factors namely behavioral factors and factors outside behavior. Consists ofPrediposing Factor in the form of knowledge attitude, Enabling Factor and Reinforcing Factor.